Bitumen Stabilised Open Graded Base Materials - Nelson, Cheah; Muthuramalingam, Jayakumar; Elhassan, Saad Hamad; Tam, Nicholas (Civil and Sustainable Urban Engineering, 2023)
Roads play a crucial role in fostering economic growth and providing social advantages in every nation. However, over time, road infrastructure can become outdated. According to studies conducted by World Highways, a road may seem to be in good condition on the surface while hiding a severe issue beneath. As a result, periodic maintenance, repairs, or modernization may be necessary for road structures. The primary purpose of this project was to investigate the effects of permeability on road base materials by removing particles and restoring strength through stabilization with bitumen. Optimum grade 60/70 bitumen was used in compliance with Malaysia JKR specifications to create a realistic case scenario. The formulation excluded open-graded road base material with particles smaller than 1.18 mm or 2.0 mm, and bitumen stabilization levels of 0%, 2%, 2.5%, and 3% were implemented to reduce the decrease in mechanical strength. The mechanical strength was determined using the California Bearing Ratio (CBR) test, while a Constant Head Method Permeability test was conducted to identify the optimal design mix with the maximum achievable permeability coefficient. The results showed that bitumen stabilization increased the mechanical strength of the road base material, with the highest result compensating for the drop by 8.7%. With open-graded road base material, the permeability can be increased by up to 17.2%. Therefore, open-graded road foundation material with bitumen as a binder for stabilization can be used in the construction of pavements in Malaysia, an area with relatively high rainfall intensity.